2014
DOI: 10.1136/bjophthalmol-2013-304777
|View full text |Cite
|
Sign up to set email alerts
|

The impact of intermittent exotropia and surgery for intermittent exotropia on myopic progression among early school-aged children with myopia

Abstract: Whether patients with intermittent exotropia underwent surgical correction for intermittent exotropia did not influence the rate of myopic progression. There was no significant difference in the rate of myopic progression between patients with accompanying intermittent exotropia and myopia and those with myopia alone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
2
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 36 publications
0
14
2
1
Order By: Relevance
“…In a study of 210 early school-aged children, Shin et al 4 observed no difference in the rate of myopic progression in those with or without intermittent exotropia, irrespective of whether they underwent surgery for the exotropia.…”
Section: The Impact Of Intermittent Exotropia and Surgery For Exotropmentioning
confidence: 97%
“…In a study of 210 early school-aged children, Shin et al 4 observed no difference in the rate of myopic progression in those with or without intermittent exotropia, irrespective of whether they underwent surgery for the exotropia.…”
Section: The Impact Of Intermittent Exotropia and Surgery For Exotropmentioning
confidence: 97%
“… 10 Surgical correction of intermittent exotropia during ages 6–15 years did not alter the rate of myopia progression, thereby suggesting that myopic refractive error might be very common in intermittent exotropia. 10 14 …”
Section: Concomitant Strabismusmentioning
confidence: 99%
“…7,21 Furthermore, a recent 6-year-long prospective study found no change in myopic shift in children aged 7-12 years who underwent successful bilateral lateral rectus muscle recession. 22 The therapeutic implication of these findings is that some patients with poorly controlled intermittent exotropia may be rescued from strabismus surgery by small amounts of over-minus treatment to clear up vision and fortify binocular alignment. We may discover that we have been inadvertently under-minusing our patients with intermittent exotropia by not over-minusing them.…”
Section: Both Convergence and Accommodation Are Normally Necessary Fomentioning
confidence: 99%